Replication Data for: A multi-pathogen screening of captive reindeer (Rangifer tarandus) in Germany based on serological and molecular assays - Sánchez Romano, Javier; Wiegmann, Lisa; Obiegala, Anna; Nymo, Ingebjørg H.; Ancin-Murguzur, Francisco Javier; Li, Hong; Król, Nina; Pfeffer, Martin; Tryland, Morten (DataverseNO, 2019)
A dataset for multi-pathogen screening of captive reindeer (Rangifer tarandus) in Germany based on serological and molecular assays. Abstract: Captive reindeer in German zoos and wildlife parks live outside their natural geographic range and are exposed to a variety of viral, bacterial and protozoan pathogens, some host-specific and some which they are not exposed to in their native habitat. Reindeer blood samples and ticks collected in 2013 from 125 reindeer at 16 different zoological facilities were available from a previous study. The aims of this study were to assess the serological status of these animals with regards to various microorganisms as well as to test ticks (Ixodes ricinus) and blood samples for the presence of Anaplasma spp. DNA in order to evaluate the exposure of captive reindeer in Germany to a variety of pathogens. Antibodies were detected by ELISA (seropositive/tested, prevalence, confidence interval) against alphaherpesvirus (24/119, 20.3 %, CI: 13.9-28.3), bluetongue virus (BTV; 4/119, 3.4 %, CI: 1.0-8.7), gammaherpesvirus (7/119, 5.9 %, CI: 2.7-11.9), pestivirus (5/118, 4.2 %, CI: 1.6-9.8), Schmallenberg virus (SBV; 70/118, 59.3 %, CI: 50.3-67.8), smooth Brucella spp. (1/118; 0.9 %, CI: 0-5.1), Neospora caninum (5/118, 4.2 %, CI: 1.6-9.8) and Toxoplasma gondii (62/119, 52.1 %, CI: 43.2-60.9). These results confirmed the exposure of reindeer to all tested pathogens. Moreover, real-time PCR for Anaplasma phagocytophilum was performed on whole blood samples from reindeer (n = 123) and 49 ticks (Ixodes ricinus) collected from 22 reindeer in seven different facilities. The samples were tested with real-time PCR and DNA of A. phagocytophilum was detected in 17 reindeer (13.8 %) and 15 ticks (30.6 %). Three of the five reindeer with ticks having A. phagocytophilium DNA also had such DNA in the blood. These results indicate that captive reindeer may be susceptible to several ruminant pathogens that they hitherto had no known exposure to through their natural geographical distribution and habitats. Further, captive reindeer may serve as reservoir hosts for pathogens circulating in local domestic, captive and wild ruminant species and populations and arthropod vectors.